Biomaterials for Tissue Engineering and Regeneration (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Biomaterials are an integral component of tissue engineering, and their development is crucial to the progress of new and efficient approaches in the regenerative medicine of bone, cartilage, tendons and ligaments, skin, soft-tissue wounds, cardiac muscle, vascular tissues, and neural tissues.Polymer-based biomaterials are extensively studied in the field of tissue engineering due to their biocompatible and biodegradable properties. This Special Issue is devoted to recent developments of synthetic and/or natural biomaterial scaffolds, hydrogels, polypeptides, polymer-based composites, and composites based on polymers and inorganic materials, such as bioactive ceramics and glasses. New technologies (e.g., bioprinting, additive manufacturing, etc.) used to form biomaterials for tissue engineering of three-dimensional (3D) constructs are of particular interest.